2014
DOI: 10.1007/978-3-319-10488-1_19
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal Modes Beyond Kerr

Abstract: The quasinormal modes (QNMs) of a black hole spacetime are the free, decaying oscillations of the spacetime, and are well understood in the case of Kerr black holes. We discuss a method for computing the QNMs of spacetimes which are slightly deformed from Kerr. We mention two example applications: the parametric, turbulent instability of scalar fields on a background which includes a gravitational QNM, and the shifts to the QNM frequencies of Kerr when the black hole is weakly charged. This method may be of us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…In order to solve the above equation and obtain the frequency shift δω, we shall apply a technique that Mark, Yang, Zimmerman, and Chen first developed for studying perturbations to Kerr-Newman black holes [44,45] and was later applied to near-extremal black holes to investigate turbulent-like instabilities [46]. In particular, these studies have verified the validity of this method under a variety of different scenarios.…”
Section: A Perturbative Methods For Solving Coupled Wave Equationsmentioning
confidence: 99%
“…In order to solve the above equation and obtain the frequency shift δω, we shall apply a technique that Mark, Yang, Zimmerman, and Chen first developed for studying perturbations to Kerr-Newman black holes [44,45] and was later applied to near-extremal black holes to investigate turbulent-like instabilities [46]. In particular, these studies have verified the validity of this method under a variety of different scenarios.…”
Section: A Perturbative Methods For Solving Coupled Wave Equationsmentioning
confidence: 99%
“…For example, in Paper I we showed that slowly rotating Kerr BHs can be accommodated within the formalism. Recent work on higher-derivative corrections to the Kerr geometry [76] and on QNM frequencies of rotating solutions for small coupling [53,54] may allow us to make progress on the calculation of QNMs in modified gravity for rotating BH remnants, such as those observed by the LIGO/Virgo collaboration [77]. Related attempts at parametrizing deviations from the Kerr QNM spectrum [78,79] made use of the connection between the stability of null geodesics and QNMs [80][81][82].…”
Section: Conclusion and A Computational Recipementioning
confidence: 99%
“…Even if GR is the correct theory of gravity, matter fields can couple with each other, and the perturbations of these fields will in general be coupled. This happens, for instance, in the Einstein-Maxwell system [49][50][51][52][53][54][55] or for axionic fields in charged BH backgrounds [10,[56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…The EVP method makes use of an original technique for applying perturbation theory to zeroth order solutions which are not square-integrable. This method can be (and recently has been [22][23][24]) applied to other problems in theoretical physics.…”
Section: Introductionmentioning
confidence: 99%